2010
DOI: 10.1007/s10822-010-9321-0
|View full text |Cite
|
Sign up to set email alerts
|

Consensus model for identification of novel PI3K inhibitors in large chemical library

Abstract: Phosphoinositide 3-kinases (PI3Ks) inhibitors have treatment potential for cancer, diabetes, cardiovascular disease, chronic inflammation and asthma. A consensus model consisting of three base classifiers (AODE, kNN, and SVM) trained with 1,283 positive compounds (PI3K inhibitors), 16 negative compounds (PI3K non-inhibitors) and 64,078 generated putative negatives was developed for predicting compounds with PI3K inhibitory activity of IC(50) < or = 10 microM. The consensus model has an estimated false positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In consequence, it has enjoyed substantial uptake (Nikora 2005;Camporelli 2006;Flikka et al 2006;Orhan and Altan 2006;Lasko et al 2006;Hunt 2006;Ferrari and Aitken 2006;Birzele and Kramer 2006;Kunchevaa et al 2007;Lau et al 2007;Masegosa et al 2007;Wang et al 2007;Garcia et al 2008;Tian et al 2008;Kurz et al 2009;Leon et al 2009;Shahri and Jamil 2009;Simpson et al 2009;Affendey et al 2010;Garc铆a-Jim茅nez et al 2010;Hopfgartner et al 2010;Liew et al 2010). …”
Section: Aodementioning
confidence: 99%
“…In consequence, it has enjoyed substantial uptake (Nikora 2005;Camporelli 2006;Flikka et al 2006;Orhan and Altan 2006;Lasko et al 2006;Hunt 2006;Ferrari and Aitken 2006;Birzele and Kramer 2006;Kunchevaa et al 2007;Lau et al 2007;Masegosa et al 2007;Wang et al 2007;Garcia et al 2008;Tian et al 2008;Kurz et al 2009;Leon et al 2009;Shahri and Jamil 2009;Simpson et al 2009;Affendey et al 2010;Garc铆a-Jim茅nez et al 2010;Hopfgartner et al 2010;Liew et al 2010). …”
Section: Aodementioning
confidence: 99%
“…These individual (constituent) classifiers, which were referred to as base classifiers or base models in the manuscript, form the ''bottom layer'' where the ensemble method is applied on. The ensemble method has shown better performances of varying degree in quantitative structure-activity relationship (QSAR) studies [30][31][32][33][34] and quantitative structuretoxicity relationship (QSTR) studies [35][36][37][38] compared to predictions from a single classifier. There is an assortment of approaches to generate multiple models that form the base classifiers of an ensemble model [39].…”
Section: Introductionmentioning
confidence: 99%
“…[6] Although AD is of great importance, compared with other aspects of QSAR, e.g. variable selection, [7][8][9] modeling techniques, [10][11][12] model validation, [13][14][15] model application, [16][17][18] the study on AD is still not enough. In the past years, some interesting studies have been reported, [19][20][21][22][23][24][25][26][27][28][29][30] but the problem of AD definition has not been well resolved so far.…”
Section: Introductionmentioning
confidence: 99%